(untitled) (Eurasian Journal of Ecology, 2022)
Persian walnut (Juglans regia L.) is one of the most economically important nut crops. In Kazakhstan, the wild-growing population of Juglans regia is registered in the south of the country and is protected on the territory of the Sairam-Ugam State National Natural Park. As a result of expeditions in 2018-2019 136 accessions of Juglans regia were described according to the descriptors of the International Plant Genetic Resources Institute, fruits of 73 accessions of walnuts were collected, which are highly diverse in terms of size, shape and weight of nuts, kernel yield, color and texture of the shell and other parameters. To conserve the biodiversity of Juglans regia, the efficient cryopreservation technique has been developed for isolated embryonic axes. After surface disinfection with 0.1% mercuric chloride solution and rinsing with sterile distilled water, the embryonic axes were desiccated under laminar flow 1 hour to moister content of 12.1%, placed in cryovials, and immersed in a Dewar vessel with liquid nitrogen. In 72.4% of embryonic axes after cryogenic storage, plant recovery was noted on the Driver-Kuniyuki walnut medium with 1 mg/l 6-benzylaminopurine and 0.01 mg/l indolylbutyric acid. A cryogenic collection of 73 Juglans regia accessions has been established. For the first time, the genetic material of Juglans regia, growing in Kazakhstan, has been stored in a cryogenic bank at -196°C. Key words: Juglans regia L., walnut, cryopreservation, cryobank, isolated embryonic axes